Terapia de espejo en la recuperación motora post accidente cerebro vascular - Jessica Carolina, Villafuerte Guaraca (2021)
ABSTRACT The present research work developed in a bibliographic review modality, which exposes the use of mirror therapy in post-stroke patients. The cerebrovascular accident causes an affectation of the half body opposite to the injured part of the brain. Mirror therapy created the visual illusion that the affected limb is moving normally by reflecting on the healthy limb, activating the mirror neurons of the nervous system to imitate and execute the movement that observed. The application of mirror therapy in the country is scarce due to the lack of knowledge of the effects that this technique has on patients who have suffered a stroke, however, of 74 articles found, 3 adapted to the study using the inclusion criteria and exclusion, in addition to complying with a score equal to or greater than 6 according to the PEDro scale, the articles are in languages such as English and Portuguese; Through research, an attempt made to demonstrate the effectiveness of mirror therapy in motor recovery after stroke. The databases with the highest results of scientific articles PubMed, Scielo, Elsevier and Cochrane. The collected items are from the year 2010 to the year 2020. Once the research has been completed after the respective discussion of different authors, the proposed objective of defining the effects of mirror therapy in the physiotherapeutic treatment of motor recovery in patients with stroke reached, by means of the compilation and analysis of bibliographic collections with rigor scientific. Key words: Mirror neurons, Stroke, Recovery of function, Rehabilitation. Reviewed by: Mgs. Maritza Chávez Aguagallo ENGLISH PROFESSOR c.c. 0602232324